(untitled) (Homoeopathy for All, 2024)
Pancreas is a gland that makes digestive enzymes and hormones like insulin that controls blood sugar. The enzymes are secreted into the intestine to help digest food. It is roughly six inches long, nestled deep in the abdomen, between the stomach and spine. The pancreas is composed of two cell types, namely exocrine and endocrine cells. The former helps break down food, while the latter makes insulin hormone.